2021
DOI: 10.2147/jmdh.s329628
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualisations of Leadership and Relevance to Health and Human Service Workforce Development: A Scoping Review

Abstract: Purpose: This scoping review was undertaken to determine leadership definitions and approaches relevant to health and human service (H&HS) workforce development. This review provides a preliminary analysis of the potential size and scope of available research literature to inform ongoing research with the ultimate aim to inform a future systematic review in relation to leadership development interventions. Methods: Following the methodology proposed by Arksey and O'Malley and using PRISMA-ScR, a systematic sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 122 publications
(185 reference statements)
0
15
0
Order By: Relevance
“…Transactional leadership is based on a mutual exchange between leader and employees (e.g., rewarding previously negotiated objectives) 8 , while transformational leadership addresses the leader's promotion of intrinsic motivation and communication of vision 9 . Both theories are well-studied, established and complement each other theoretically and in practice 4 . Methodologically, the reviewed interventions combine various learning methods, e.g., seminars, lectures, group work, mentoring, multi-source and action-based feedback.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Transactional leadership is based on a mutual exchange between leader and employees (e.g., rewarding previously negotiated objectives) 8 , while transformational leadership addresses the leader's promotion of intrinsic motivation and communication of vision 9 . Both theories are well-studied, established and complement each other theoretically and in practice 4 . Methodologically, the reviewed interventions combine various learning methods, e.g., seminars, lectures, group work, mentoring, multi-source and action-based feedback.…”
Section: Introductionmentioning
confidence: 91%
“…In the last decades, leadership has become an increasingly important topic in medicine, with the need to especially train physician leaders 1 , 2 . In graduate education, the ‘physician as leader’ is conceptualized in the CanMEDS roles, but no standard for leadership training in primary care and other specialties has been developed 3 , 4 . Four reviews comparing various leadership programs showed considerable diversity regarding target groups (physicians of various experience levels), specialty focus (primary care and other fields), program aims (e.g., clinical leadership for integrated primary care), theoretical foundation and methodological approaches (scoping, narrative vs. systematic reviews) 4 7 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations